Diplomatic Amateurs or Qualified Professionals? Profiling the American Ambassador - Calin, Costel; Fitzpatrick, Kathy R. (White House Studies, 2013)
Are U.S. ambassadors qualified to lead America’s diplomatic missions abroad? This age-old question—often raised but seldom seriously considered by diplomacy scholars— is the focus of this study, which examined the professional credentials of American ambassadors appointed by former U.S. President George W. Bush. The article explores the relationship between the professional status of U.S. ambassadors and the power status and economic importance of host countries. The results showed that preferred destinations for amateur ambassadors were mostly Western European countries and countries with which the United States has large economic exchanges. Professional ambassadors were mostly appointed to African and Asian countries and to countries that have lower trade with the United States. The vast majority of semiprofessional diplomats were appointed to the most powerful countries.
Keywords: AMERICAN ambassadors; BUSH, George W. (George Walker), 1946-; DIPLOMATIC & consular service; GOVERNMENT missions; INTERNATIONAL relations; PRESIDENTS of the United States; dept.psc